2011
DOI: 10.1007/s00394-011-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant, anti-inflammatory and immunomodulating properties of an enzymatic protein hydrolysate from yellow field pea seeds

Abstract: Enzymatic protein degradation confers anti-oxidant, anti-inflammatory and immunomodulating potentials to pea proteins, and the resulted peptides could be used as an alternative therapy for the prevention of inflammatory-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 43 publications
5
78
1
Order By: Relevance
“…Pea protein hydrolysate plus carbohydrate induces both higher insulin and glucagon responses than soybean protein hydrolysate plus carbohydrate [28]. Additionally, pea protein hydrolysate may have antioxidant, anti-inflammatory, and immunomodulating properties that may confer benefits to the patient [29]. As expected, preoperative insulin levels were higher in the intervention group than in the control group patients, who had lower serum insulin levels in response to an overnight fast [11].…”
Section: Discussionsupporting
confidence: 52%
“…Pea protein hydrolysate plus carbohydrate induces both higher insulin and glucagon responses than soybean protein hydrolysate plus carbohydrate [28]. Additionally, pea protein hydrolysate may have antioxidant, anti-inflammatory, and immunomodulating properties that may confer benefits to the patient [29]. As expected, preoperative insulin levels were higher in the intervention group than in the control group patients, who had lower serum insulin levels in response to an overnight fast [11].…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the meta-analysis showed that diet rich in legumes, such as a variety of beans, peas, and some seeds other than soy decreases total and low-density lipoprotein (LDL) cholesterol [20]. Different legumes have been identified as sources of ACE-inhibitory and antioxidative peptides, mainly soybean [21][22][23][24], chickpea and pea [25][26][27][28].…”
Section: Biological Activities Of Plant Proteinsmentioning
confidence: 99%
“…Other legume protein hydrolysates have shown inhibition of NO production by activated macrophages (Ndiaye et al, 2012).…”
Section: Effect Of Lphs On the Nitrite Productionmentioning
confidence: 99%
“…The increase in the incidence of inflammation related disorders has led to the search of proteins and peptides with anti-inflammatory properties (Ndiaye, Vuong, Duarte, Aluko, & Matar, 2012). There is evidence of the ability of distinct food compounds, including proteins, to modulate inflammation in experimental models involving macrophages (Boesch-Saadatmandi et al, 2011;Hämäläinen et al, 2011;Yu, Correll, & Vanden Heuvel, 2002).…”
Section: Introductionmentioning
confidence: 99%